Commentary essay on "blueprinting the service company – managing service processes efficiently". Issue 3 (3rd July 2019) - Fließ, Sabine; Kleinaltenkamp, Michael
ABSTRACT: In 2004, our article "Blueprinting the service company – managing service processes efficiently" was published in the Journal of Business Research. We were invited by the editor, Arch G. Woodside, to comment on the success of the article and the further development of the topics addressed, which we are most happy to do. The comment is organized as follows: first, we will summarize the main contributions of our original work. In the second part, we will address further developments of the original article's central issues, thus, highlighting the evolution of the service blueprinting method. In the third and final part, we will discuss the relevance of service blueprinting in the light of recent developments in service theory.